RETRACTED: The Collective Effect of MIP-3α and FL Promotes Dendritic Cell Function Within the Immune Microenvironment of Murine Liver Cancer - Zhao, Haichao; Chen, Changzhou; Chen, Xidong; Yang, Chuanli; Zhang, Donglin; Li, Yanjun; Zhao, Haoliang; He, Jiefeng (Frontiers in Oncology, 2021)
Hepatocellular carcinoma is a highly malignant and lethal tumor. In addition to surgery, immunotherapy is currently a more effective treatment for hepatocellular carcinoma. The tumor immune microenvironment (TIME) largely determines the efficacy of cancer immunotherapy. Based on the universal targeting of TIME modulators in clinical treatment, TIME modulators are promising targets for tumor immunotherapy. We investigated the effect of a double gene expression vector (recombinant galactose-terminal glycol-poly-L-lysine coupled MIP-3α-FL) on dendritic cell (DC) regulation within the immune microenvironment of mice with liver cancer. H22 cells were transfected with a recombinant MIP-3α-FL plasmid to induce DC differentiation and chemotaxis. The effects of transfection were investigated by flow cytometry following the modified Boyden's method. Cytokine-induced killer (CIK) cell co-culture revealed changes in the antigen presentation ability of DCs. Further, tumor-bearing mice were injected with the recombinant double gene vector via the tail vein. We compared the survival time, tumor volume, weight of the mice, as well as the number and phenotype of tumor-infiltrating DCs (TIDCs) between groups. The supernatant of transfected H22 cells promoted the phenotypic maturation of DCs, enhancing their chemotaxis. Further, treated DCs promoted the cytokine secretion and killing ability of CIK cells. The survival time of mice injected with the double gene vector was significantly prolonged, while their tumor weight and volume were relatively reduced. Flow cytometry revealed that the number of TIDCs (as well as CD80 and CD86 expression) in the MouseMIP-3α-FL group, were significantly higher than in the control group. The combination of MIP-3α and FL can significantly promote DC aggregation, maturation, and enhance their antigen presentation ability. The coupling of the double gene vector with glycosylated polylysine can improve the precise targeting of the liver and inhibit tumor growth in vivo, providing a novel approach for cell therapy in liver cancer.